Tourism and the implications of climate change issues and actions - Schott, Christian (Emerald, 2010)
This volume provides a valuable platform for knowledge exchange between different disciplines and for learning from both theory and practice in the context of tourism and climate change. The academic and case-study chapters in this volume provide a contextualization of tourism and climate change science, an examination of issues and actions in different countries and with different tourism consumers, and looks at the supply, adaptation and innovation of tourism products. Subjects examined are as diverse as: the European hotel sector; the North American cruise tourism industry; New Zealand youth hostels and campervans; Australia's tourism industrys GHG footprint; climate forecasts in the Baltic States; heat stress conditions in Spain; the Tourism Earth Lung initiative in Sri Lanka; and online discussions in cybercommunities. The different disciplinary perspectives presented in this volume include anthropology, climatology, climate change studies, economics, environmental sustainability, hospitality, policy and planning, psychology, scenario planning, and transport studies and contributions originate from eight developed countries across three continents.
Keywords: Tourism -- Environmental aspects.; Climatic changes.; elektronické knihy; electronic books